The postulates of Liberalism and the Crisis Punish Power State - Lourenço, Cristina S. Alves (2016)
The liberalism introduced a new way of thinking and feeling man. This should be the right holder and so could not be more at the mercy of an arbitrary and inhuman power which employed religious persecution and restrictions. With the introduction of these new postulates that today are essential to living together in society and the development of man as a being of rights. However, the reverse of what happened in the so called Liberal State, where citizens worried about their front guarantees to the interventionist state, because they saw it as an object; Today, the citizen is also concerned with their guarantees, but based on other grounds, not now sees itself as an object, but as a victim going to require an increase in security. Similarly, the creation of new risks inherent in a civilization that wants advanced in technological terms, tends to no longer limit the punitive power of the state before an actual serious injury of an important legal interest and lacking in criminal custody, with therefore, the state tends to increase their repressive power inflicting often basic principles of a state that wants guarantor. Forming a paradox, on the one hand citizens wanting security giving up more and more of their freedom, and on the other the state “guarantor” abridging increasingly freedoms, surpassing the limits imposed by the various principles and generating a great legal uncertainty. To put problems, this study adopted the deductive method in which it was observed that: (i) the use of criminal laws blank, without a parameter to follow, violating the Principle of Legality; (ii) the inclusion of rampant laws many times have vague and imprecise content, violating the Principle of Legality and Minimum Intervention; (iii) the proliferation of dangerous offenses (abstract and concrete), rising acts preparatory to the offenses, thus causing a breach of the Minimum Intervention Principle; (iv) a change in the legal and concept that gives the individual interests in favor of collective interests, seeking a newfoundation; (v) the face of these changes, the penalty tends to be higher and exclusionfactor but no more effective and criminal law, tends to lower the graphic of the pyramid and turn into material ratio of society.